Draft Annual Plan (1968-69) Part-II (Statements) Union Territory of Pondicherry - Planning Commission (Planning Commission, 1971)
Union Territory of Pondicherry Summary statement of Annual Plan outlay 1968-69 - Territory Plan, Distribution of outlay under selected Sub-heads of development Details by Schemes/Projects/ Programmers.
Union Territory of Pondicherry
Union Territory of Pondicherry
Keywords: Summary statement of Annual Plan outlay 1968-69 - Territory Plan; Distribution of outlay under selected Sub-heads of development Details by Schemes/Projects/ Programmers; Production Estimates and Selected Programme targets Draft Annual Plan - 1968-69; Allied Programme; Dairying and Milk Supply; Warehouse and Marketing; Corporation Community Development